No Fukushima Dai-ichi derived plutonium signal in marine sediments collected 1.5–57 km from the reactors. (November 2017) - Wendel, C.C.S.; Lind, O.C.; Fifield, L.K.; Tims, S.G.; Salbu, B.; Oughton, D.H.
Abstract: Based on AMS analysis, it is shown that no Pu signals from the Fukushima accident could be discerned in marine sediments collected 1.5–57 km away from the Fukushima Da-ichi power plant (FDNPP), which were clearly influenced by accident-derived radiocesium. The 240 Pu/ 239 Pu atom ratios (0.21–0.28) were significantly higher than terrestrial global fallout (0.182 ± 0.005), but still in agreement with pre-FDNPP accident baseline data for Pu in near coastal seawaters influenced by global fallout and long-range transport of Pu from the Pacific Proving Grounds. Graphical abstract: Highlights: AMS of Pu concentrations and atom ratios in marine samples near Fukushima NPP. No Pu from Fukushima accident discerned in sediments near (1.5 km) the plant. Main source of Pu in sediments from global fallout and Pacific Proving Grounds. Low 239+240 Pu/ 137 Cs activity ratios in sediments show Fukushima accident influence.